Analyse de la matière et de la forme des questions de français sur la page niveau débutant A1 d’Apprendre.tv5monde.com - Cahyandaru Hakiki, Gladiza; Vitri Widayanti, Diah (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
Digital learning materials are abundant on the internet. The Apprendre.TV5Monde.com site is an innovation essential to learning the French language. This research aims to describe the material’s suitability and the form of the questions for four DELF A1 language skills. It is descriptive research using data sheets and tables to analyze and calculate the number of matches between the material and the form of the practice questions. Research shows that the seven themes containing material and question forms relating to the material improve three language skills except oral production. This is not available due to the absence of the appropriate tool. In total, 442 questions correspond to 112 materials spread over seven themes. Each material presented is evaluated to monitor the success of the learning objective. We can conclude that this page is recommended as a support for learning French for beginners.